Life style: progress in measuring life style and its relation with other psychological concept - Sánchez López, María del Pilar (2001)
Studies on life styles ha ve driven us to consider three studies which analyse the concept and its relationship with other psychological variables. The first study presents an analysis of the activities carried out by a person, asan operational definition of life styles using ADIT self-registering (Self-Registeringof Time Distribution, SRTD), considering individuals who interact with subject in those activities. In the second study, modifications to the original self-record are suggested; eg, the sectionthat registers where and with whom are carried out the activities was eliminated. In the third study, the relationships among life styles, life satisfaction and personality variables are analysed. Therewere 84 persons in the sample assigned to 6 groups, depending on the relationships among these three concepts, as was previously suggested by other studies